Evaluasi Kenyamanan Termal dan Estetika Berbasis Analisis Tapak dan Persepsi User Taman Kota Depok - Nadhifa, Dalila Helmy; Budiarti, Tati; Manningtyas, Rosyidamayanti (Jurnal Lanskap Indonesia, 2024)
The condition of Parks in Depok City has become unmaintained since the covid-19 pandemic due to restrictions on the number of visitors. On the other hand, a comfortable park can improve health. This study identifies existing conditions and analyzes thermal comfort and aesthetics in Taman Lembah Gurame, Taman Lembah Mawar, and Taman Merdeka based on site analysis and users’ perceptions. Evaluation of thermal comfort using Thermal Humidity Index (THI) analysis, while evaluation of landscape aesthetic using the Scenic Beauty Estimation (SBE) method. The perception and preference of respondents using descriptive statistical analysis methods. The THI analysis result showed that the thermal comfort of three city parks was classified as uncomfortable to very uncomfortable. However, the aesthetic assessment in Taman Lembah Gurame and Taman Lembah Mawar was highly aesthetic, while Taman Merdeka was lowly aesthetic. It could be caused by planting design, layout, and activities on-site, which makes users more tolerant of the thermal comfort of parks. Improving facilities and adding flowering plants and shady trees are needed to make city parks more comfortable, beautiful, also adaptive in the new normal era.